Changing presentation of complete hydatidiform mole at the New England Trophoblastic Disease Center over the past three decades: does early diagnosis alter risk for gestational trophoblastic neoplasia? - Sun, Sue Yazaki; Melamed, Alexander; Goldstein, Donald P.; Bernstein, Marilyn R.; Horowitz, Neil S.; Moron, Antonio Fernandes; Maesta, Izildinha [UNESP]; Braga, Antonio; Berkowitz, Ross S. (Elsevier B.V., 2015)
Objective. To compare the clinical presentation and incidence of postmolar gestational trophoblastic neoplasia (GTN) among recent (1994-2013) and historical (1988-1993) cases of complete hydatidiform mole (CHM).Methods. This study included two non-concurrent cohorts (1988-1993 versus 1994-2013) of patients from the New England Trophoblastic Disease Center (NETDC). Clinical and pathologic reports of patients diagnosed with CHM between 1994 and 2013 were reviewed. Gestational age at evacuation, features of clinical presentation, human chorionic gonadotropin (hCG) levels, and the rate of progression to GTN were compared.Results. In the current cohort (1994 to 2013) the median gestational age at diagnosis continued to decline compared to our prior cohort (1988-1993) (9 weeks versus 12 weeks). Patients from the current cohort were significantly more likely to be diagnosed prior to the 11th week of gestation (56 versus 41%, p = 0.04). Patients in the current cohort were also significantly less likely to present with vaginal bleeding (46 versus 84%, p < 0.001). Earlier diagnosis of complete mole did not result in a decrease in the rate of postmolar GTN. The frequencies of postmolar GTN in the current (1994-2013) and prior (1988-1993) cohorts were 19 and 23%, respectively. In the current cohort, even diagnosis prior to ten weeks gestation did not decrease the risk of developing GTN.Conclusions. This study indicates that complete mole continues to be diagnosed progressively earlier resulting in a further decrease in some classical presenting symptoms. However, despite earlier detection, the risk of development of postmolar GTN has not been affected. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Gestational trophoblastic disease; Gestational trophoblastic neoplasia